Republic of Moldova : Poverty Reduction Strategy Paper Annual Evaluation Report 2005; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
This Joint Staff Advisory Note provides IMF staff's assessment of the Moldova authorities' first Annual Evaluation Report (AER), which covers the period from late 2004 to early 2006. Broadly, the AER provides a candid assessment of the accomplishments and shortcomings of the past year, focusing on outcomes rather than inputs. It points to evidence of continued poverty reduction, but also highlights areas where policy implementation has been slower than originally envisaged. The AER also presents an updated description of the dynamics of poverty and inequality in Moldova.